Seamless exploitation of cell‐phone antennas for near‐field WPT by a frequency‐diplexing approach. Issue 5 (24th January 2017) - Del Prete, Massimo; Berra, Francesco; Costanzo, Alessandra; Masotti, Diego
Abstract : This paper introduces a novel solution for portable devices to exploit their existing communication antennas for bi‐directional near‐field wireless re‐charging, without compromising their far‐field properties. To demonstrate the concept, the radio‐frequencies (RF) 900/1800 MHz and 433 MHz are adopted for the far‐field communication and for the near‐field wireless recharging, respectively. First, a pair of faced, dual‐band, printed monopoles is characterized as a two‐port network over the bands of interest at several distances. Then, each antenna is fed by a frequency‐selective three‐port network, designed to simultaneously ensure data communication at the higher frequencies and wireless re‐charging at the lower one. In this way, the combined far‐field and near‐field operations of the resulting four‐port network can be optimized. A proof‐of‐concept prototype has been characterized, showing ports isolation higher than 20 dB and RF‐to‐RF power transfer efficiency between 15% and 40% for variable faced antennas distance. When a rectifier is connected to the receiving power port, the measured RF‐to‐dc link efficiency varies between 9% and 20%, with portable devices located 1 and 2 centimeters apart, and the transmitted power is 10 dBm. The simultaneous high frequency communication is verified with slightly reduced performance.